2020
DOI: 10.4103/ija.ija_264_20
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of premixed versus succedent administration of fentanyl and bupivacaine in subarachnoid block for lower limb surgeries: A randomised control trial

Abstract: Background and Aims: Subarachnoid block is the most commonly used anaesthesia technique for lower limb surgeries. Opioids are the most commonly used adjuvants with local anesthetics (LA). Adjuvants are given premixed with LA loaded in a single syringe. This study was conducted to evaluate differences in level of sensory and motor block and incidence of hypotension whilst administering hyperbaric bupivacaine and fentanyl either in a single syringe or different syringes. The effect of administering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 14 publications
6
6
1
Order By: Relevance
“…Among the sequential groups, it was faster in Group A wherein bupivacaine H was injected first as compared to Group B where intrathecal fentanyl preceded the local anesthetic. Similar results were seen in a study done by Malhotra et al, 5 where they reported faster onset of sensory/motor block in the sequential group (2.9±1 min/3.6±1.1 min) and delayed in the premixed group (6.3±1.5 min/7.2±1.5 min). The findings of our study can be logically explained as follows-in sequential groups since bupivacaine H and fentanyl were injected separately, due to the baricity of local anesthetic the drug spread was more toward the most dependent part of the spine in supine position, that is, around T7-T8 level, while in the premixed group, the lower baricity restricted the cephalad spread of the drugs.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Among the sequential groups, it was faster in Group A wherein bupivacaine H was injected first as compared to Group B where intrathecal fentanyl preceded the local anesthetic. Similar results were seen in a study done by Malhotra et al, 5 where they reported faster onset of sensory/motor block in the sequential group (2.9±1 min/3.6±1.1 min) and delayed in the premixed group (6.3±1.5 min/7.2±1.5 min). The findings of our study can be logically explained as follows-in sequential groups since bupivacaine H and fentanyl were injected separately, due to the baricity of local anesthetic the drug spread was more toward the most dependent part of the spine in supine position, that is, around T7-T8 level, while in the premixed group, the lower baricity restricted the cephalad spread of the drugs.…”
Section: Discussionsupporting
confidence: 91%
“…This difference might be due to the fact that fentanyl and bupivacaine as a mixture dilutes the potency of fentanyl and receptor occupancy might decrease leading to a less pronounced effect. 5 On the other hand, if fentanyl is administered separately it leads to formation of stronger bonds with the mu opioid receptors concentrated in the superficial layers of the dorsal horn in the spinal cord leading to denser and prolonged block.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, fentanyl acts on afferent nociceptive pathway leading to less haemodynamic changes. [5][6][7] Ratio of specific density of anesthetics and cerebrospinal fluid (CSF) is termed as baricity. So, hyperbaric means heavier and hypobaric means lighter than CSF.…”
Section: Introductionmentioning
confidence: 99%
“…4 Fentanyl when added to hyperbaric bupivacaine, decreases the density of solution to extent of 0.0006 which alters the spread of local anesthetics in CSF. 5 Fentanyl and hyperbaric bupivacaine are usually premixed in a single syringe before intrathecal administration. Various factor influence the spread and action of anaesthetic solution like temperature, pH, density, volume of drug, patients position and height of the patient.…”
Section: Introductionmentioning
confidence: 99%